2006
DOI: 10.1021/jo052329e
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Cyclizations of Dilithiated Oximes and Hydrazones with Epibromohydrin. Efficient Synthesis of 6-Hydroxymethyl-5,6-dihydro-4H-1,2-oxazines and Oxazolo[3,4-b]pyridazin-7-ones

Abstract: The one-pot cyclization of dilithiated oximes with epibromohydrin provided a convenient and regioselective approach to 6-hydroxymethyl-5,6-dihydro-4H-1,2-oxazines. The reaction of the latter with phosphorus tribromide resulted in a Beckmann rearrangement and formation of 5-bromomethyl-2-iminotetrahydrofurans. The reaction of dilithiated hydrazones with epibromohydrin afforded oxazolo[3,4-b]pyridazin-7-ones, which were formed by a novel domino cyclization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Similar rearrangement has been recently described by the Langer group in a series of 3-aryl-6-(hydroxymethyl)-substituted SCOE 191 (Scheme ) . These oxime ethers upon the action of phosphorus tribromide are converted to tetrahydrofurans 192 in poor yields.…”
Section: Chemical Properties Of Scoesupporting
confidence: 60%
See 1 more Smart Citation
“…Similar rearrangement has been recently described by the Langer group in a series of 3-aryl-6-(hydroxymethyl)-substituted SCOE 191 (Scheme ) . These oxime ethers upon the action of phosphorus tribromide are converted to tetrahydrofurans 192 in poor yields.…”
Section: Chemical Properties Of Scoesupporting
confidence: 60%
“…Langer and co-workers , reported that anions of oximes 49 obtained in situ from the dilithiated derivatives of oximes 51 and epibromohydrine (Scheme , eq 2) undergo cyclization with the participation of the epoxide group and the oxygen atom of the oximino group, giving rise to dihydrooxazines 50 in moderate to good yields. If substituent R 1 ≠ H, the products are obtained as a mixture of diastereomers (dr ∼ 1:1) …”
Section: Synthesis Of Six-membered Cyclic Oxime Ethers 1 Andmentioning
confidence: 99%
“…1,2‐Oxazines are also available by the cyclization of alkenyl‐substituted oximes using NBS,16 diphenyl diselenide,17 acid,18 UV light,19 and iodine 20. Cyclization of γ‐sulfonyloximes,21 γ‐chlorooximes22 and γ,δ‐epoxyoxime23 by using base is also a method for the preparation of 1,2‐oxazines. Other synthetic approaches to 1,2‐oxazines rely on Lewis acid‐catalyzed cyclization of allene‐substituted oxime24 and acid‐catalyzed cyclization of cyclopropyloxime 25.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, epibromohydrin ( 6 ) has been employed in the synthesis of 6-hydroxymethyl-5,6-dihydro-4 H -1,2-oxazines . In that respect, the reaction of epibromohydrin ( 6 ) with dilithiated oximes 277 , generated from oximes 276 with n -butyllithium, led to the selective formation of 1,2-oxazines 279 in 30–81% yield by initial nucleophilic substitution of epibromohydrin ( 6 ) to form intermediate 278 , which cyclizes to the dihydro-1,2-oxazine derivatives 279 (Scheme ).…”
Section: Applications Of Epichlorohydrin and Epibromohydrin In The Sy...mentioning
confidence: 99%